2007
DOI: 10.1007/s11664-007-0222-5
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Dissolution and Shear Properties of the Joints between Bi-Ag Alloys and Cu Substrates for High-Temperature Soldering Applications

Abstract: The present study investigated interfacial reactions between Cu substrates and Bi-Ag alloys during soldering. Without forming intermetallic compounds (IMCs), the molten solder grooved and further penetrated along the grain boundaries (GBs) of the Cu substrate. An increase in Ag content enhanced GB grooving, raised the dissolution rate and also the amount of dissolved Cu in molten Bi. A stoichiometric Cu-Bi phase formed isothermally in liquid solders and considerably affected the Cu dissolution kinetics. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…They concluded that, in the case of pure bismuth, the dissolution rate is close to the rate of grooving, whereas once the liquid reaches saturation level the grooving rate is greater than the total rate of dissolution. Song et al 11 studied the dissolution of copper in pure Bi, Bi-2.5Ag, and Bi-11Ag (wt.%). They found that the dissolution of Cu is correlated with the initial concentration of Ag in the solder, i.e., under the same time-temperature conditions, Bi-11Ag dissolves the highest and pure Bi the lowest amounts of copper.…”
Section: Wetting and Interfacial Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that, in the case of pure bismuth, the dissolution rate is close to the rate of grooving, whereas once the liquid reaches saturation level the grooving rate is greater than the total rate of dissolution. Song et al 11 studied the dissolution of copper in pure Bi, Bi-2.5Ag, and Bi-11Ag (wt.%). They found that the dissolution of Cu is correlated with the initial concentration of Ag in the solder, i.e., under the same time-temperature conditions, Bi-11Ag dissolves the highest and pure Bi the lowest amounts of copper.…”
Section: Wetting and Interfacial Chemistrymentioning
confidence: 99%
“…In particular, no interlayers can be distinguished and dissolution of Cu substrate in Bi-Ag alloy is observed. 6,11 From a practical point of view, it would be valuable to investigate the effect of the initial Cu content in the alloy on its wetting of Cu substrate and the microstructure of the soldersubstrate interface.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases soldering was performed by the use of ZnCl 2 -NH 4 Cl flux. In the work of Song et al [10] the lap joint was used to determine the shear strength of joint fabricated by the use of Bi-11Ag solder on copper and obtained results showed the values from 20 to 36 MPa and for the Pb-5Sn solder the shear strength between 14 and 18 MPa was measured. Fractographic analysis was applied in the study of fracture morphology by use of SEM observations.…”
Section: Measuring the Shear Strength Of Jointsmentioning
confidence: 99%
“…In case of Bi-11Ag solder, the fracture occurred on the intermetallic boundary. Coarsening of Cu substrate is elucidated by the capability of Bi-11Ag solder to roughen the surface and to penetrate to the grain boundaries [17,10]. In case of Au-20Sn solder, tearing out of a part of the Cu substrate also occurred (Fig.…”
Section: Measuring the Shear Strength Of Jointsmentioning
confidence: 99%
See 1 more Smart Citation